2012
DOI: 10.1186/1471-2393-12-127
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual misoprostol versus standard surgical care for treatment of incomplete abortion in five sub-Saharan African countries

Abstract: BackgroundIn low-resource settings, where abortion is highly restricted and self-induced abortions are common, access to post-abortion care (PAC) services, especially treatment of incomplete terminations, is a priority. Standard post-abortion care has involved surgical intervention but can be hard to access in these areas. Misoprostol provides an alternative to surgical intervention that could increase access to abortion care. We sought to gather additional evidence regarding the efficacy of 400 mcg of subling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
44
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 12 publications
9
44
1
1
Order By: Relevance
“…These results confirm that 400 mcg sublingual misoprostol effectively evacuates the uterus for most women experiencing incomplete abortion [7]. The high level of satisfaction and overall tolerability of the side effects also attests to the ease of use of this method.…”
Section: Discussionsupporting
confidence: 67%
“…These results confirm that 400 mcg sublingual misoprostol effectively evacuates the uterus for most women experiencing incomplete abortion [7]. The high level of satisfaction and overall tolerability of the side effects also attests to the ease of use of this method.…”
Section: Discussionsupporting
confidence: 67%
“…A recent study utilizing misoprostol for PAC in Senegal showed high efficacy and acceptability [2]. Numerous other studies have produced similar results [3–9].…”
Section: Introductionmentioning
confidence: 83%
“…Some of these conditions, particularly induced abortion, can be managed by medical therapy as an alternative to surgery. However, evidence shows superior outcomes from surgery, including studies from LMICs . Surgical backup is crucial in case the treatment is unsuccessful.…”
Section: Methodsmentioning
confidence: 99%